AlGaInP yellow-green LED epitaxial wafer with high brightness, low leakage and high reliability
By introducing N-type electron delay layer and multi-quantum well layer designs into the AlGaInP short-wavelength LED epitaxial structure, the problems of reduced luminescence efficiency and reduced reliability caused by electron leakage and Mg diffusion are solved, and the AlGaInP yellow-green LED epitaxial sheet with high brightness, low leakage and high reliability are achieved.
Patent Information
- Application Number
- CN202411977272.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing AlGaInP short-wavelength LED epitaxial structure has reduced luminous efficiency and reduced reliability due to electron leakage and Mg diffusion under high temperature conditions, forming a vicious cycle, limiting the performance improvement and stability of the device.
The improved AlGaInP yellow-green LED epitaxial sheet structure is adopted, including an N-type electron retardation layer, a multi-quantum well layer, a P-type AlInP restriction layer and a P-type GaP current expansion layer. Through the superlattice structure and Al content gradient design, electron leakage and Mg diffusion are suppressed, and luminescence efficiency and device stability are optimized.
It significantly improves the probability of recombination between electrons and holes, reduces carrier leakage and non-radiation recombination, improves the brightness and reliability of the device, and performs more stably in high temperature conditions.
Smart Images

Figure CN119855313A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of LEDs, and in particular to an AlGaInP yellow-green LED epitaxial wafer with high brightness, low leakage and high reliability. Background Art
[0002] AlGaInP yellow-green LED chips provide efficient, energy-saving and environmentally friendly lighting solutions in the fields of home lighting, commercial lighting and public lighting. In addition, it can also be used to manufacture high-resolution, high-color reproduction display screens to enhance the realism and delicacy of the visual experience. At the same time, yellow-green LED chips have high-speed and efficient data transmission capabilities, which are of great significance to the development of modern communication networks in the field of optical communications. The realization of these excellent performances depends on the unique advantages of the AlGaInP material system and its complex epitaxial structure design. The rationality of the epitaxial structure directly affects the performance and application range of the chip.
[0003] The existing quaternary AlGaInP short-wavelength LED epitaxial structure usually includes: GaAs substrate, sequentially grown N-type GaAs buffer layer, N-type GaInP etching stop layer, N-type GaAs ohmic contact layer, N-type AlGaInP current spreading layer, N-type AlInP confinement layer, multi-quantum well layer, P-type AlInP confinement layer, P-type GaP current spreading layer and P-type GaP ohmic contact layer. This structure has good luminous efficiency and high reliability in practical applications. However, in the process of developing towards short wavelengths, the material system faces many challenges, especially the change of Al content has a significant impact on device performance.
[0004] As the Al content in the multi-quantum well layer increases, the AlGaInP material gradually changes from a direct band gap to an indirect band gap, resulting in the need for phonons in the luminescence process, a significant decrease in the quantum efficiency of composite luminescence, and a decrease in the recombination probability of electrons and holes. In addition, since the migration speed of electrons is much higher than that of holes, a large number of electrons are prone to leak into the P region under non-equilibrium conditions, thereby increasing non-radiative recombination. This not only leads to a decrease in luminescence efficiency, but also causes a large amount of heat accumulation in the interface layer area, narrowing the bandgap width of the semiconductor, and further exacerbating the electron leakage phenomenon.
[0005] On the other hand, under high-temperature working conditions, the Mg element in the P-type doping easily diffuses into the quantum well region, forming impurity energy levels, capturing electrons, and further increasing non-radiative recombination, resulting in a continuous decrease in the luminous efficiency of the quantum well. In addition, as the device lighting time increases, this effect gradually accumulates, the brightness of the device continues to decay, and the reliability is significantly reduced. This coupling effect of electron leakage and Mg diffusion forms a vicious cycle, which seriously restricts the performance improvement and stability of short-wavelength AlGaInP LED devices. Summary of the invention
[0006] In order to solve the above problems, the present invention provides an improved high-brightness yellow-green wavelength quaternary AlGaInP epitaxial wafer.
[0007] The specific technical solutions of the present invention are as follows:
[0008] An AlGaInP yellow-green LED epitaxial wafer with high brightness, low leakage and high reliability, characterized by comprising the following layer structures grown in sequence on a GaAs substrate:
[0009] N-type GaAs buffer layer, thickness is 150-200nm, Si element doping concentration is 1×10 18 -2×10 18 atoms / cm 3 , dopant is Si 2 H 6 ;
[0010] N-type GaInP etching stop layer, thickness is 100-200nm, Si element doping concentration is 1×10 18 -3×10 18 atoms / cm 3 , dopant is Si 2 H 6 ;
[0011] N-type GaAs ohmic contact layer, thickness is 30-100nm, carrier concentration is 3×10 18 -6×10 18 atoms / cm 3 , dopant is Si 2 H 6 ;
[0012] N-type AlGaInP current spreading layer, with a thickness of 1000-2500nm and a composition of (Al x Ga 1-x ) 0.5 In 0.5 P, 0.6≤x≤1, carrier concentration is 13×10 18 atoms / cm 3 , dopant is Si 2 H 6 ;
[0013] N-type electron delay layer, with a multi-layer superlattice structure, composed of Al y Ga 1-y InP(0.6≤y≤0.8),Al 0.5 In 0.5 P.Al 0.65 In 0.35The thickness of each sublayer in the N-type electron delay layer increases layer by layer along the epitaxial growth direction, and is specifically determined according to the following formula: the thickness of the nth layer = initial thickness + (maximum thickness / total number of layers) × (n-1), where:
[0014] Al y Ga 1-y The maximum thickness of the InP sublayer is 10-20nm, and the initial thickness is 3-5nm;
[0015] Al 0.5 In 0.4 The maximum thickness of the P sublayer is 15-25nm, and the initial thickness is 5-7nm;
[0016] Al 0.65 In 0.35 The maximum thickness of the P sublayer is 5-10nm, and the initial thickness is 1-3nm;
[0017] The total number of layers is 10-25 pairs, and the Si element doping concentration is 1×10 18 -2×10 18 atoms / cm 3 , dopant is Si 2 H 6 ;
[0018] N-type AlInP confinement layer, thickness is 150-350nm, carrier concentration is 7×10 17 -2×10 18 atoms / cm 3 , dopant is Si 2 H 6 ;
[0019] The multi-quantum well layer includes 30 to 80 pairs of quantum wells and quantum barriers, wherein:
[0020] Each quantum well is 3-5nm thick;
[0021] The thickness of the quantum barrier decreases layer by layer from 10-15nm to 4-6nm along the growth direction;
[0022] The Al content of the quantum barrier is from Al a Ga 1-a InP (0.6≤a≤0.7) gradually increases to Al b Ga 1-b InP(0.8≤b≤0.9);
[0023] The P-type AlInP limiting layer has a thickness of 250-600 nm. In the P-type AlInP limiting layer, a Mg diffusion barrier layer with a thickness of 50-150 nm is provided along the thickness direction thereof. The thickness of the Mg diffusion barrier layer is 50-150 nm, and the Mg element doping concentration is 1×10 17 -3×10 17 atoms / cm 3 , the remaining carrier concentration is 8×10 17 -1.5×10 18 atoms / cm 3 , dopant is Cp 2 Mg;
[0024] P-type GaP current spreading layer, divided into:
[0025] The bottom low Mg doped layer has a thickness of 200-300nm and a Mg doping concentration of 3×10 17 -5×10 17 atoms / cm 3 , the top high Mg doped layer has a thickness of 300-1500nm and a Mg doping concentration of 4-8×10 18 atoms / cm 3 , dopant is Cp 2 Mg;
[0026] P-type GaP ohmic contact layer, thickness is 30-100nm, carrier concentration is 0.5-2E20, dopant is CBr 4 or CCl 4 .
[0027] Preferably, the thickness of the AlGaInP current spreading layer is 1500-2000 nm, and the range of x is 0.7-0.9.
[0028] Preferably, the total number of layers of the N-type electron delay layer is 15-20 pairs, and the thickness of each sub-layer is designed according to the formula: thickness of the nth layer = initial thickness + maximum thickness / total number of layers × (n-1).
[0029] Preferably, the dopant of the N-type electron delay layer is Si 2 H 6 , the doping concentration is 1.5×10 18 -2×10 18 atoms / cm 3 .
[0030] Preferably, the number of quantum wells and quantum barriers in the multi-quantum well layer is 40-60 pairs, the quantum well thickness of the multi-quantum well layer is 4-5nm, the quantum barrier thickness of the multi-quantum well layer gradually decreases from 10nm to 5nm, and the Al content in the direction pointing to the P-type AlInP confinement layer increases from Al to a Ga 1-a InP (0.65≤a≤0.7) gradually increases to Al b Ga 1-b InP (0.85≤b≤0.9).
[0031] Preferably, the Mg diffusion barrier layer in the P-type AlInP limiting layer has a thickness of 80-120 nm and a doping concentration of 1.5×10 17 -2.5×10 17 atoms / cm 3 If the Mg diffusion barrier layer is too thick or the doping is too low, it will affect hole injection. If the thickness is too thin or the doping is too high, it will not be able to block Mg.
[0032] Preferably, the Mg diffusion barrier layer is arranged at one-third of the distance from the P-type AlInP confinement layer close to the multi-quantum well layer, and the thickness and doping concentration of the Mg diffusion barrier layer are adjusted. If it is far away from the quantum well and close to the P-type GaP current expansion layer, the Mg will diffuse a lot and will not work beyond the barrier layer, resulting in reliability problems; if it is closer to the quantum well layer, it will lead to insufficient hole injection and affect the quantum injection efficiency.
[0033] Preferably, the low-doping layer thickness of the P-type GaP current spreading layer is 250-300 nm, and the Mg element doping concentration is 4×10 17 -5×10 17 atoms / cm 3 .
[0034] Preferably, the thickness of the high-doped layer of the P-type GaP current spreading layer is 500-1000 nm, and the Mg element doping concentration is 5×10 18 -7×10 18 atoms / cm 3 .
[0035] Preferably, the thickness of the P-type GaP ohmic contact layer is 50-80 nm, and the dopant is CBr 4 .
[0036] Through the above technical scheme, the present invention achieves the following beneficial effects:
[0037] Improve electron migration efficiency and limit electron leakage: The introduction of an N-type electron delay layer significantly reduces electron mobility and leakage of electrons to the P region through superlattice structure and Al content gradient changes, thereby improving the recombination efficiency of electrons and holes. Through the thickness gradient design, the electron delay layer further optimizes the electron transmission path in the gradually increasing thickness, effectively reducing the occurrence of non-radiative recombination.
[0038] Optimize the luminous efficiency of the multi-quantum well layer: The thickness of the quantum barrier layer is gradually reduced from 10-15nm to 4-6nm, which effectively improves the hole injection efficiency. At the same time, the gradient of the Al content in the quantum barrier layer is increased to gradually increase the bandgap width, optimize the efficiency of the simultaneous arrival of electrons and holes in the luminescent layer, and thus increase the probability of radiation recombination. The purpose of this design is to adjust the position of the main luminescent layer to the center of the quantum well layer to improve the luminous efficiency.
[0039] Inhibit Mg diffusion and improve device stability: A low-doped Mg diffusion barrier layer is set in the P-type AlInP layer to effectively reduce the diffusion of Mg into the light-emitting layer through the barrier effect, and reduce the non-radiative recombination caused by the Mg impurity energy level. The thickness and doping concentration of the barrier layer are precisely designed to take into account both inhibiting Mg diffusion and maintaining hole injection efficiency.
[0040] Improve the performance of the P-type GaP current spreading layer: The P-type GaP current spreading layer is designed to be divided into two parts, the lower layer is low-doped to reduce the probability of Mg diffusing into the light-emitting layer, and the upper layer is highly doped to enhance the current spreading capability and hole injection efficiency, further improving the luminescence performance of the device.
[0041] Significantly improve device brightness and reliability: A variety of innovative designs work together to significantly increase the recombination probability of electrons and holes, reduce carrier leakage and non-radiative recombination, and greatly improve the brightness and reliability of AlGaInP short-wavelength LEDs, especially under high temperature conditions. More stable performance.
[0042] In summary, the present invention solves the problems of brightness attenuation and insufficient device reliability in the prior art, so that the AlGaInP yellow-green LED chip of the present invention has significant advantages in terms of luminous efficiency and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 It is a structural schematic diagram of the AlGaInP yellow-green LED epitaxial wafer with high brightness, low leakage and high reliability of the present invention.
[0044] Figure 2 This is a relationship diagram of the thickness of each sub-layer of the N-type electron delay layer in Example 1 of the present invention gradually increasing linearly with the number of layers.
[0045] Figure 3 It is a schematic diagram of the structure of the P-type AlInP confinement layer in the present invention.
[0046] Figure 4 It is a schematic structural diagram of the P-type GaP current spreading layer in the present invention.
[0047] Figure 5 This is a graph showing the relationship between the forward voltage and forward current of a 14mil yellow-green LED (embodiment of the present invention and conventional embodiment).
[0048] Figure 6 14mil yellow-green LED wavelength-current curve (embodiment of the present invention and conventional).
[0049] Figure 7 This is a graph showing the relationship between the luminous intensity and forward current of a 14mil yellow-green LED (the embodiment of the present invention and the conventional one).
[0050] Figure 8 This is a comparison of the aging of ΔLOP of a 14mil yellow-green LED at room temperature and at high temperature over time (the embodiment of the present invention and the conventional one). DETAILED DESCRIPTION
[0051] Preferred embodiments of the present invention are given below in conjunction with the accompanying drawings to illustrate the technical solutions of the present invention in detail.
[0052] Example 1
[0053] like Figure 1 As shown, this embodiment provides an AlGaInP yellow-green LED epitaxial wafer with high brightness, low leakage and high reliability, and its specific structure and parameters are as follows:
[0054] N-type GaAs buffer layer L1: thickness 200nm, doping concentration 1.5×10 18 atoms / cm 3 , dopant is Si 2 H 6 ;
[0055] N-type GaInP etching stop layer L2: thickness 150nm, doping concentration 2×10 18 atoms / cm 3 , dopant is Si 2 H 6 ;
[0056] N-type GaAs ohmic contact layer L3: thickness 50nm, carrier concentration 4×10 18 atoms / cm 3 , dopant is Si 2 H 6 ;
[0057] N-type AlGaInP current spreading layer L4: thickness 2000nm, composition (AlxGa1-x) 0.5 In 0.5 P, where x = 0.7 and the carrier concentration is 2 × 10 18 atoms / cm 3 ;
[0058] N-type electron delay layer L5: a multi-layer superlattice structure is used, with a total of 20 pairs of layers, and the thickness of each sub-layer increases in sequence along the growth direction. Figure 2 As shown:
[0059] The maximum thickness of the AlyGa1-yInP sublayer is 15nm, and the initial thickness is 4nm;
[0060] Al 0.5 In 0.5 The maximum thickness of the P sublayer is 20 nm, and the initial thickness is 6 nm;
[0061] Al 0.65 In 0.35 The maximum thickness of the P sublayer is 8nm, and the initial thickness is 2nm;
[0062] N-type AlInP confinement layer L6: thickness 300nm, doping concentration 1×10 18 atoms / cm 3 ;
[0063] The electron delay layer uses AlGaInP, and the mobility changes with the change of Al element content. The greater the Al element content, the lower the mobility. In particular, the last layer of the three groups has a high Al element content and a higher bandgap width, which has a stronger restriction on electrons and can effectively reduce the electron mobility.
[0064] Multi-quantum well layer L7: contains 60 pairs of quantum wells and quantum barriers, with specific parameters:
[0065] The quantum well thickness is 4nm, and the quantum barrier thickness decreases linearly from 12nm to 5nm, which can improve hole injection;
[0066] The Al content is from Al a Ga 1-a InP (a = 0.65) gradually increases to Al b Ga 1-b InP (b = 0.85); As the Al content increases, the bandgap width of the quantum barrier layer gradually increases, which can slow down the migration speed of electrons. Its equivalent efficiency is to move the position of the main light-emitting layer to the center of the light-emitting layer, increase the simultaneous rate of electrons and holes reaching the light-emitting layer, and increase the probability of radiation recombination;
[0067] P-type AlInP confinement layer L8: thickness is 500nm, such as Figure 3 As shown, the bottom P-type AlInP barrier layer L71 is provided with a thickness of 50 nm and a doping concentration of 1×10 17 atoms / cm 3 Mg diffusion barrier layer L72, upper P-type AlInP confinement layer L73;
[0068] P-type GaP current spreading layer L9: Figure 4 As shown, it is divided into two parts:
[0069] Bottom low Mg doped layer L91: thickness is 200nm, doping concentration is 4×10 17 atoms / cm 3 ;
[0070] Top high Mg doped layer L92: thickness 1000nm, doping concentration 6×10 18 atoms / cm 3 ;
[0071] P-type GaP ohmic contact layer L10: thickness 50nm, carrier concentration 1×10 20 atoms / cm 3 , dopant is CBr 4 .
[0072] Example 2
[0073] Based on Example 1, the following parameters were adjusted:
[0074] N-type electron delay layer: the total number of layers is changed from 20 pairs to 15 pairs;
[0075] Multi-quantum well layer: the number of quantum well barrier pairs is reduced from 60 pairs to 50 pairs;
[0076] P-type AlInP limiting layer: Mg diffusion barrier layer thickness is adjusted to 100nm, doping concentration is 2×10 17 atoms / cm 3 .
[0077] P-type GaP current spreading layer: low Mg doping layer thickness changed to 300nm
[0078] Example 3
[0079] Based on Example 2, the parameters are further optimized:
[0080] N-type electron delay layer: using 18 pairs of superlattice structure;
[0081] Multi-quantum well layer: the Al element content of the quantum barrier gradually increases from AlaGa1-aInP (a=0.7) to AlbGa1-bInP (b=0.9); the thickness of the quantum barrier decreases linearly to 4nm;
[0082] P-type GaP current spreading layer: low Mg doping layer thickness changed to 250nm
[0083] Test experiment:
[0084] 1. Device preparation and testing
[0085] The epitaxial wafers of the conventional structure and Examples 1, 2 and 3 were prepared by a metal organic compound vapor phase epitaxial deposition (MOCVD) method.
[0086] The light output power and spectral distribution of the device were measured using electroluminescence (EL) spectroscopy.
[0087] The carrier leakage characteristics of the device are measured through the IV curve to evaluate the leakage current of the device.
[0088] High temperature aging test is used to evaluate the reliability and brightness attenuation of devices under high temperature conditions.
[0089] 2. Experimental results: Figure 5-Figure 8 As shown in Table 1, the data is when the test current is 60mA.
[0090]
[0091] Parameter Description:
[0092] VF(V): Forward voltage, in volts (V).
[0093] WLD (nm): Wavelength Dominant, the unit is nanometer (nm).
[0094] LOP (mcd): Luminous Output Power, in millicandela (mcd).
[0095] It can be seen that:
[0096] Brightness enhancement effect:
[0097] The optical output power of the device in Example 1 is increased by about 15% compared with the conventional structure, and maintains a stable output at 60°C.
[0098] Examples 2 and 3 further optimize the Al content and the Mg diffusion inhibition effect, and the brightness is increased by 18% and 20% compared with the traditional structure.
[0099] Carrier leakage suppression:
[0100] Experiments show that the N-type electron delay layer effectively suppresses electron leakage. Under the same MQW logarithm condition, the saturation current of Example 1 is 10 mA higher than that of the conventional structure.
[0101] High temperature stability:
[0102] After continuous aging for 1000 hours at 85°C with a current of 75 mA, the brightness of Example 1 decayed by only 4%, while the brightness of the conventional device decayed by as much as 17%.
[0103] The brightness attenuation of Examples 2 and 3 in this test was 3% and 2.5% respectively, showing higher reliability.
[0104] 3. Experimental conclusion
[0105] Through the above examples and experimental data verification, the AlGaInP yellow-green LED epitaxial wafer provided by the present invention has the following advantages:
[0106] Significantly improve the brightness and luminous efficiency of the device;
[0107] Effectively inhibit carrier leakage and non-radiative recombination, and reduce leakage current;
[0108] Improve the working stability and reliability of devices in high temperature environments;
[0109] By designing a Mg diffusion barrier layer, the brightness decay of the device can be further delayed.
Claims
1. A high brightness, low leakage, high reliability AlGaInP yellow-green LED epitaxial wafer, characterized in that: The structure comprises the following layers grown sequentially on a GaAs substrate: N-type GaAs buffer layer, thickness is 150-200nm, Si element doping concentration is 1×10 18 -2×10 18 atoms / cm 3 , the dopant is Si2H6; N-type GaInP etching stop layer, thickness is 100-200nm, Si element doping concentration is 1×10 18 -3×10 18 atoms / cm 3 , the dopant is Si2H6; N-type GaAs ohmic contact layer, thickness is 30-100nm, carrier concentration is 3×10 18 -6×10 18 atoms / cm 3 , the dopant is Si2H6; N-type AlGaInP current spreading layer, with a thickness of 1000-2500nm and a composition of (Al x Ga 1-x ) 0.5 In 0.5 P, where 0.6≤x≤1, and the carrier concentration is 1×10 18 -3×10 18 atoms / cm 3 , the dopant is Si2H6; N-type electron delay layer, with a multi-layer superlattice structure, composed of Al y Ga 1-y InP(0.6≤y≤0.8),Al 0.5 In 0.5 P.Al 0.65 In 0.35 The thickness of each sublayer in the N-type electron delay layer increases layer by layer along the epitaxial growth direction, and is specifically determined according to the following formula: the thickness of the nth layer = initial thickness + (maximum thickness / total number of layers) × (n-1), where: Al y Ga 1-y The maximum thickness of the InP sublayer is 10-20nm, and the initial thickness is 3-5nm; Al 0.5 In 0.4 The maximum thickness of the P sublayer is 15-25nm, and the initial thickness is 5-7nm; Al 0.65 In 0.35 The maximum thickness of the P sublayer is 5-10nm, and the initial thickness is 1-3nm; The total number of layers is 10-25 pairs, and the Si element doping concentration is 1×10 18 -2×10 18 atoms / cm 3 , the dopant is Si2H6; N-type AlInP confinement layer, thickness is 150-350nm, carrier concentration is 7×10 17 -2×10 18 atoms / cm 3 , the dopant is Si2H6; The multi-quantum well layer includes 30-80 pairs of quantum wells and quantum barriers, each pair consisting of a quantum well and a quantum barrier, where: Each quantum well is 3-5nm thick; The thickness of the quantum barrier decreases layer by layer from 10-15nm to 4-6nm along the growth direction; The Al content of the quantum barrier is from Al a Ga 1-a InP (0.6≤a≤0.7) gradually increases to Al b Ga 1-b InP (0.8≤b≤0.9); The P-type AlInP limiting layer has a thickness of 250-600 nm. In the P-type AlInP limiting layer, a Mg diffusion barrier layer with a thickness of 50-150 nm is provided along the thickness direction thereof. The Mg diffusion barrier layer has a thickness of 50-150 nm and a doping concentration of 1×10 17 -3×10 17 atoms / cm 3 , the remaining carrier concentration is 8×10 17 -1.5×10 18 atoms / cm 3 , the dopant is Cp2Mg; P-type GaP current spreading layer, divided into: The bottom low Mg doped layer has a thickness of 200-300nm and a Mg doping concentration of 3×10 17 -5×10 17 atoms / cm 3 , the top high Mg doped layer has a thickness of 300-1500nm and a Mg doping concentration of 4×10 18 -8×10 18 atoms / cm 3 , the dopant is Cp2Mg; P-type GaP ohmic contact layer, thickness is 30-100nm, carrier concentration is 0.5-2E20, dopant is CBr4 or CCl4.
2. The AlGaInP yellow-green LED epitaxial wafer according to claim 1, characterized in that: The total number of layers of the N-type electron delay layer is 15-20 pairs, and the thickness of each sub-layer is designed according to the formula: nth layer thickness = initial thickness + maximum thickness / total number of layers × (n-1).
3. The AlGaInP yellow-green LED epitaxial wafer according to claim 1, characterized in that: The dopant of the N-type electron delay layer is Si2H6, and the doping concentration is 1.5×10 18 -2×10 18 atoms / cm 3 .
4. The AlGaInP yellow-green LED epitaxial wafer according to any one of claim 1, characterized in that: The number of quantum wells and quantum barriers in the multi-quantum well layer is 40-60 pairs, the quantum well thickness of the multi-quantum well layer is 4-5nm, the quantum barrier thickness of the multi-quantum well layer gradually decreases from 10nm to 5nm, and the Al content in the direction from the quantum well layer to the P-type AlInP confinement layer decreases from Al a Ga 1-a InP (0.65≤a≤0.7) gradually increases to Al b Ga 1-b InP (0.85≤b≤0.9).
5. The AlGaInP yellow-green LED epitaxial wafer according to any one of claim 1, characterized in that: The Mg diffusion barrier layer in the P-type AlInP confinement layer has a thickness of 80-120 nm and a doping concentration of 1.5×10 17 -2.5×10 17 atoms / cm 3 .
6. The AlGaInP yellow-green LED epitaxial wafer according to any one of claim 1, characterized in that: The Mg diffusion barrier layer is arranged at one third of the distance measured from the side of the P-type AlInP confinement layer close to the multi-quantum well layer.
7. The AlGaInP yellow-green LED epitaxial wafer according to any one of claim 1, characterized in that: The low-doping layer thickness of the P-type GaP current spreading layer is 250-300nm, and the Mg doping concentration is 4×10 17 -5×10 17 atoms / cm 3 .
8. The AlGaInP yellow-green LED epitaxial wafer according to any one of claim 1, characterized in that: The thickness of the high-doped layer of the P-type GaP current spreading layer is 500-1000nm, and the Mg doping concentration is 5×10 18 -7×10 18 atoms / cm 3 .
9. The AlGaInP yellow-green LED epitaxial wafer according to any one of claim 1, characterized in that: The thickness of the P-type GaP ohmic contact layer is 50-80 nm, and the dopant is CBr4.
10. The AlGaInP yellow-green LED epitaxial wafer according to any one of claim 1, characterized in that: The thickness of the N-type AlGaInP current spreading layer is 1500-2000 nm, and the range of x is 0.7-0.9.
Citation Information
Patent Citations
Light emitting diode epitaxial wafer capable of emitting red and yellow lights and preparation method for light emitting diode chip
CN105529382A
Yellow-green-light light emitting diode and preparation method therefor
CN106025023A
Epitaxial wafer for green-yellow light emitting diode and manufacturing method thereof
CN106057997A
940nm reversed polarity infrared LED epitaxial wafer and preparation method thereof
CN117976791A
Efficiency of quantum in yellow -green light LED is improved epitaxial structure
CN208738288U
Cited By
High-efficiency red light plant illumination light-emitting diode epitaxial wafer and manufacturing method thereof
CN120475825A